Forced exercise increases muscle mass in EAE despite early onset of disability - Patel, D. I; White, L. J; Lira, V. A; Criswell, D. S (Physiological research, 2016)
We aimed to determine whether 10 days of treadmill exercise can increase skeletal muscle mass and intramuscular concentrations of brain derived neurotrophic factor (BDNF) and nerve growth factor (NGF) in experimental autoimmune encephalomyelitis (EAE). Forty female Lewis rats were randomly assigned to either EAE sedentary (EAE-Sed), EAE exercise (EAE-Ex), Control sedentary (Con-Sed) and Control exercise (Con-Ex). Exercising animals completed a 10 day forced exercising training program. Hind limb skeletal muscles were excised and weighed with soleus muscle used for BDNF and NGF quantification. Statistical analysis was done using a one-way analysis of variance. Disability was more pronounced in the EAE-Ex group than in the EAE-Sed group. Exercising animals (EAE-Ex and Con-Ex) had significantly greater bilateral EDL, plantaris and gastrocnemius muscle mass compared to their sedentary animals (p=0.01). The EAE-Ex group had significantly higher NGF concentrations (1.98+/-0.3 pg/mg) compared to Con-Ex (0.96+/-0.07 pg/mg, p=0.003) and Con-Sed (1.2+/-0.2 pg/mg, p=0.04) groups. The main effect of exercise represented a significantly lower BDNF concentrations in the soleus of exercising animals compared to sedentary animals (p=0.03). Our study provides preliminary evidence that exercise increases skeletal muscle mass despite the early onset of disability in EAE animals.
Keywords: mozkový neurotrofický faktor; Animals; Encephalomyelitis, Autoimmune, Experimental; Muscle, Skeletal; krysa rodu Rattus; ženské pohlaví; encefalomyelitida autoimunitní experimentální; terapie cvičením; Rats, Inbred Lew; Rats; Disability Evaluation; Sedentary Behavior; nervový růstový faktor; kosterní svaly; zvířata; Exercise Therapy; kondiční příprava zvířat; Body Weight; zadní končetina; Physical Conditioning, Animal; tělesná hmotnost; Nerve Growth Factor; Brain-Derived Neurotrophic Factor; Hindlimb; potkani inbrední LEW; sedavý životní styl; posuzování pracovní neschopnosti; Female